The sent interests at Al-Hanafiyya and their contemporary applications in personal status - Almwadih, Rakan Khalaf Mahasneh (Journal of Islamic Sciences, 2023)
This research was built from an introduction and three sections, and it was based on the descriptive approach and the inductive analytical approach, and aimed mainly to clarify the truth of the interests sent when the Hanafi, and its authenticity, and to identify the approach of Imam  Abu Hanifa in the work of Palm Saleh sent through  its origins in the doctrine, and also through the branches of jurisprudence transmitted from the Imam   In the books of the doctrine, and the statement of the extent to which the interests sent when the Hanafi in some contemporary images related to personal status such as medical examination before marriage, and documentation of the marriage contract in the courts as an applied study, and the  research has concluded the most important features considered in the fact of interests sent in the Hanafi school and the extent of taking these, where it was found that the researcher that they worked this consideration by taking them the principle of approbation, which made the sections of the desirability of interest or the desirability of necessity,  He revealed that this consideration is taken into account in contemporary issues related to personal status such as medical examination before marriage, and the official documentation of marriage contracts for the preservation of rights, payment of damage and other effects. At the end of the research, a set of recommendations were presented to students of knowledge and specialists.
Keywords: Sent interest; Hanafi school; contemporary applications